Outcome of Cataract Surgery in Patients with Pseudoexfoliation - Surekha Bangal; Akshay Bhandari; Pratik Gogri (Delhi Journal of Ophthalmology, 2013)
Purpose: To study the surgical outcome & the complications encountered during & after cataract surgery in Indian patients with pseudoexfoliation. Materials & Methods: In this hospital based retrospective study, 50 patients above 50 years of age having cataract with pseudoexfoliation & having normal Intraocular Pressure (IOP) who underwent extracapsular catract surgery were included. Patients with other associated ocular pathology were excluded. Patients were followed up for various complications up to 30th postoperative day. Results: Fifty patients with pseudoexfoliation underwent extra capsular cataract surgery. Problems encountered during surgery were small nondilating pupil (26%), zonular dialysis (2%), posterior capsular rupture (6%), vitreous loss (4%), residual lens matter (10%), iridodialysis (4%) hyphema (2%). Post-operative complications were irregular pupil due to sphincterotomy (8%), significant anterior chamber reaction (30%), and exudative membrane formation (6%), corneal oedema with striate keratopathy (32%), iris pigment dispersion (16%), raised intraocular pressure (6%), posterior synechiae (2%) and intraocular lens decentration (2%). Conclusion: Patients with pseudoexfoliation are at increased risk for development of surgical and postsurgical complications. Awareness about complications and ability to manage these complications by experienced surgeon is key to success.